Efektivitas Pelaksanaan Perawatan Metode Kanguru pada Bayi Berat Lahir Rendah di Masa Pandemi COVID-19 - Siti Muthoharoh; Yeni Rustina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effectiveness of the implementation of Kangaroo Method Care (PMK) during the COVID-19 pandemic. The method used is a literature review through article searches in the ScienceDirect, EBSCOhost, Embase, Google Scholar, Wiley and Sage Publications databases. The results showed that there were two main themes found, namely the factors that influenced the implementation of PMK during the COVID-19 pandemic and the benefits of implementing early PMK. In conclusion, the implementation of PMK during the COVID-19 pandemic experienced obstacles, namely the reduction of PMK practice hours or even elimination altogether, so LBW did not get great benefits from the implementation of PMK. Keywords: Low Birth Weight Babies, COVID-19 Pandemic, Kangaroo Method Care